Twice‐ rather than once‐daily basal insulin is associated with better glycaemic control in Type 1 diabetes mellitus 12 months after skills‐based structured education in insulin self‐management. Issue 8 (28th May 2015) - Hopkinson, H. E.; Jacques, R. M.; Gardner, K. J.; Amiel, S. A.; Mansell, P.
Abstract Aim This study investigates the relationship between basal insulin regimen and glycaemic outcomes 12 months after skills‐based structured education in the UK Dose Adjustment for Normal Eating (DAFNE) programme for Type 1 diabetes mellitus. Method Retrospective analysis of data from 892 DAFNE participants from 11 UK centres. Results Mean HbA1c 12 months after DAFNE was lower in those using twice‐ rather than once‐daily basal insulin after correcting for differences in baseline HbA1c, age and duration of diabetes; difference –2 (95% CI –3 to –1) mmol/mol [–0.2 (–0.3 to –0.1)%], P = 0.009. The greatest fall in HbA1c of –5 (–7 to –3) mmol/mol [–0.4 (–0.6 to –0.3)%], P < 0.001 occurred in those with less good baseline control, HbA1c ≥ 58 mmol/mol, who switched from once‐ to twice‐daily basal insulin. There was no difference in the 12‐month HbA1c between users of glargine, detemir and NPH insulin after correcting for other variables. Relative risk of severe hypoglycaemia fell by 76% and ketoacidosis by 63% 12 months after DAFNE. The rate of severe hypoglycaemia fell from 0.82 to 0.23 events/patient year in twice‐daily basal insulin users. In the group with greatest fall in HbA1c, the estimated relative risk for severe hypoglycaemia in twice‐daily basal insulin users versus once daily at 12 months was 1.72 (0.88–3.36, P = 0.110). Conclusion After structured education in adults with Type 1 diabetes mellitus, use of basal insulin twice rather than once daily was associated with lower HbA1c, independent of insulin type, with significant reductions in severe hypoglycaemia and ketoacidosis in all groups.